Self-access English Language Enrichment Hub (SELEH): the OER booster / Mah Boon Yih - Mah, Boon Yih (Academy of Language Studies, 2022)
Since the COVID-19 epidemic seized the world by storm in early 2020, e-learning has been embraced as the only way to secure the continuation of academic activity. In response to the economic and social activities lockdown, which has resulted in a halt in face-to-face teaching and learning activities, Assoc. Prof. Dr Mah Boon Yih, a Microsoft Innovative Educator Expert (2021 -2022) and Microsoft Innovative Educator Master Trainer, initiated Self-access English Language Enrichment Hub or SELEH, which is accessible at https://www.wecwi.com/post/seleh .SELEH is one of the Open Educational Resources (OER) licensed under CC BY -NC-SA 4.0. It is formulated based on RACQAIL attributes, which stands for Relevance, Accuracy, Clarity, Quality, Accessibility, Interactivity, and Licensing. It provides flexibility and equitable opportunity to utilise learning resources, resulting in increased accessibility and openness in education (Ehlers, 2011). According to UNESCO, OER are "teaching, learning, and research materials in any medium-digital or otherwise-that are in the public domain or have been released under an open licence that permits no-cost access, use, adaptation, and redistribution by others with no or limited restrictions."